2004
DOI: 10.1093/ndt/gfh393
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in HIV-1-infected patients and its impact on renal and cardiovascular integrity

Abstract: Our data do not demonstrate any association between the presence of hypertension and antiretroviral therapy or immune status. However, hypertension seems to have a high impact on the existing risk for premature cardiovascular disease. Furthermore, overt proteinuria is frequent in HIV-1 infection with hypertension and might be due to hypertensive nephrosclerosis as well as yet undefined renal disease in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
41
2
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 17 publications
7
41
2
3
Order By: Relevance
“…Such conditions affected 13-48% of our subjects, rates similar to those published from other studies of HIV-infected patients. 3,14,15 Our work also demonstrates that many relationships between traditional risk factors and chronic diseases in the general population (e.g., obesity and hypertension) persist for HIV-infected patients. Furthermore, although much has been made of the contribution of antiretroviral therapy toward development of these conditions, our study indicates that the risk conferred by traditional factors is often comparable toand occasionally greater than-that due to antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 53%
“…Such conditions affected 13-48% of our subjects, rates similar to those published from other studies of HIV-infected patients. 3,14,15 Our work also demonstrates that many relationships between traditional risk factors and chronic diseases in the general population (e.g., obesity and hypertension) persist for HIV-infected patients. Furthermore, although much has been made of the contribution of antiretroviral therapy toward development of these conditions, our study indicates that the risk conferred by traditional factors is often comparable toand occasionally greater than-that due to antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 53%
“…Highly active antiretroviral therapy has been linked to hypertension in a few but not all studies. In a retrospective analysis by Cattelan et al (39), a significant increase in both systolic and diastolic BP was noted in HIV-infected patients who were on long-term therapy with indinavir compared with baseline BP before protease inhibitor therapy; however, Jung et al (40) observed no significant difference between hypertensive and normotensive patients when comparing current as well as total duration of specific antiretroviral drugs or combination regimen. Because we excluded all patients with hypertension in the analysis, it is unlikely that the renal vascular damage observed in our study is linked to highly active antiretroviral therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the risk of cardiovascular disease was significantly higher in patients with MS. Hadigan et al (2001) Before the advent of HAART, hypertension was often reported in patients infected with HIV (Iwuala, 2008). Recent studies highlight hypertension increasingly observed in patients infected with HIV on antiretroviral therapy (Gazzaruso et al, 2003;Jung et al, 2004). Blood pressure up than 130/85 mmHg was found in 13.9% of our study population receiving ARV treatment.…”
Section: Resultsmentioning
confidence: 61%
“…Muhammad et al (2013) reported a prevalence of 17% of hypertension cases in HIV patients mainly on NNRTI-based HAART during 6-84 months. In Western countries, many studies showed hypertension proportion among HIV patients on HAART ranging from 13% to 34% (Gazzaruso et al, 2003;Jung et al, 2004;Bergersen et al, 2003;Medina-Torne et al, 2012;Savès et al, 2003).…”
Section: Resultsmentioning
confidence: 99%